Relationship between Building Manager Behavior and Building Conditions with the Level of Cockroach Density at Soekarno Hatta Airport - Abudin, Syafii; Martini, Martini; Nurjazuli, Nurjazuli (Poltekkes Kemenkes Palu, 2024)
Cockroaches have a role as mechanical vectors for several diseases so they must be controlled so as not to interfere with human health. The purpose of this study is to determine the relationship between the behavior of building managers and building conditions with cockroach density. Soekarno Hatta Airport in Tangerang City which is one of the busiest airports in the world. The sample in this study amounted to 100 people in 100 buildings. This study used an analytical observational design with a cross-sectional design. The variables studied are the behavior of building managers in the form of knowledge, attitudes, and actions whose data is taken through questionnaires, and variables of building conditions in the form of building sanitation, types of buildings, and building construction whose data is taken through observation and measurement in the field. Based on the results of the Chi-Square analysis, shows that the behavior of building managers in the form of knowledge (p = 0.021), attitudes (p = 0.014), and action (p = 0.035) with the level of cockroach density has a significant relationship The variable of building condition has a Chi-Square test value on building sanitation (p = 0.012) which means it has a significant relationship. Building managers should be given the understanding to improve the value of behavior and improve building sanitation by keeping cockroach density levels low regularly.